Menimbang Gadai Emas sebagai Instrumen Investasi Syariah - Ahmad Chairul Hadi (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2012)
The increasing of gold prices and high interest of the community to invest in gold responded by Islamic banking through Islamic gold pawning services with the term